Republic of Poland : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2010)
The Selected Issues paper on Poland underlies that as the only European Union economy to avoid outright recession during the crisis, Poland is likely to attract renewed risk appetite. Poland could become one of the main recipients of capital inflows. This could lead to excessive exchange-rate appreciation, which would undermine competitiveness. The volatility of capital flows into Poland has been lower during both the boom and crisis periods, in part owing to timely introduction in the boom period of countercyclical macroprudential measures.